1166. Evaluating the Impact of the 2016 Candidemia Guidelines on the Incidence of Ocular Complications of Candidemia. (31st December 2020) - Hillenbrand, Molly; Apewokin, Senu
Abstract: Background: The incidence of Candida bloodstream infections has risen over the last several decades. Complications of candidemia include endogenous fungal endophthalmitis which can result in devastating outcomes including vision loss. In 2015, the IDSA guidelines were updated to recommend echinocandins as initial therapy for candidemia. Given the poor ocular penetration of echinocandins there has been some concern this change may portend an increased incidence of ocular complications in candidemic patients. We sought to examine whether patients who received empiric echinocandin therapy developed higher rates of ophthalmic complications of candidemia. Methods: We identified patients in our healthcare system who had blood cultures positive for Candida species and a completed ophthalmology consult between January 1, 2014 and April 30, 2019. Chi-squared analysis was used to compare antifungal prescribing patterns before and after release of the updated IDSA guidelines. We assessed whether the switch to empiric echinocandin therapy as directed by the guidelines was associated with higher rates of abnormal eye exams. Results: 47 patients treated before the guideline change were compared to 57 patients treated after the guideline change. There was no significant difference in age, gender, or comorbid diabetes and hypertension between the groups. Before the guideline change, 24/47 (51%) of patients received eye-penetrating antifungals. This decreased to 21/57 after the updated guideline (37%, p=0.21). The percentage of patients with positive eye exams was nearly equal before and after the updated guidelines, 10/47 (21%) before vs 13/57 (22%) after (p=1). After the guideline change, 7/21 (33%) of the patients treated with penetrating antifungals had positive eye exams vs 6/36 (16%) who received echinocandins (p=0.19). Conclusion: Echinocandins are known to have poor ocular penetration yet our data demonstrate no change in the incidence of ophthalmic complications of candidemia after the 2016 guideline endorsed echinocandins as empiric therapy. The prevalence of positive eye exams throughout our study period was 22%, suggesting ongoing utility for these exams. Ongoing investigation is necessary to confirm and further study these findings. Disclosures: All Authors : No reported disclosures